Perbandingan Kadar Flavonoid dan Aktivitas Antioksidan pada Kulit Bawang Merah (Allium ascalonicum) dan Kulit Bawang Bombay (Allium cepa) - Maria Putri Kirana; Restry Sinansari; Diana Diana; Maria Anabella Jessica (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The utilization of natural resources, especially from agricultural waste, has great potential in the development of functional products because the waste still contains beneficial bioactive compounds. Onions are known to be rich in phytochemical content and high antioxidant activity, and the skin is known to contain higher phytochemical content compared to the onion bulb. This makes onion skin very potential to be used as a functional ingredient. This study aims to determine the flavonoid levels and antioxidant activity of shallot peel (Allium ascalonicum) and onion peel (Allium cepa). Determination of flavonoid levels was carried out using UV-Vis spectrophotometry with a colorimetric method, and determination of antioxidant activity using a microplate reader with a DPPH (2,2-diphenyl-1-picryhydrazyl) method. Determination of antioxidant activity samples was seen from qualitative test results expressed in IC50 values ​​or inhibitory concentrations. Based on the results of research data, shallot peel (Allium ascalonicum) has an average flavonoid content of 176.2472 mgQE/g with an IC50 value of 54.8949 ppm, and onion peel (Allium cepa) has an average flavonoid content of 207.5205 mgQE/g with an IC50 value of 46.2653 ppm.